Mending Fences, Building Bridges: The Effect of Relationship by Objectives on Conflict - Hebdon, Robert; Mazerolle, Maurice (Relations industrielles / Industrial Relations, 1995)
During the last decade, researchers have developed new theoretical approaches to human resources. The growing preoccupation with the human resource function in the organization has been praised publicly by practitioners. Over the years, this preoccupation has been responsible for changing behavioral patterns as well as human resource management activities. In 1978, the author conducted a study investigating the human resource function, based on the perceptions of directors and human resource managers. The present study considers the following question: "Have the human resource function in the workplace and the general and specific perceptions of directors and human resource managers evolved over the last decade?"Three specific dimensions stand out here: the notion of the evolution of human resource in itself; the evolution in the perceptions of the participants; and the time-lag between theory and practice. From these dimensions emerge three hypotheses which revolve around three elements: participants, time and space. This study focuses on the participants' perceptions of the importance of the HR function and covers a period of ten years, 1978-1989. The study establishes a link between the theoretical evolution of the HR function and its applications.The results of this study are based on the comments of directors and human resource managers in organizations with 200 or more employees. These organizations are located in the province of Quebec and belong to the private secondary sector. The participants completed a questionnaire on general variables, such as the period of time devoted to human resources activities, the influence-authority of the parties involved, interdepartmental communication, the participants' involvement in organizational activities, the right to information and consultation. Questions were also asked on specific variables such as planning of personnel, recruitment in human resources, training and development of human resources.In our 1978 study, as in that of 1989, information was collected from workplaces representative of the population studied. The profiles of both directors and human resource managers have developed at the same rate as the organizations which employ them. In the 1989 study, however, participants are slightly younger and the academie level of the human resource manager is superior to that of his predecessors.Statistical analysis of the collected data allows us to assert that the human resource function in Quebec, including both general and specific characteristics, has progressed very slowly during the last decade. If both structure and activities of this function have increased, it has not, for all that, become more integrated in the evolution of the organization. The analysis also shows that the perception of all participants is more or less the same in 1989 as it was in 1978.Moreover, integration of the human resource function theoretical concepts did not follow the growth rate expected by both researchers and administrators. Does this mean that, in the last decade, actual developments in human resources lagged behind the level of discourse? An affirmative answer to this question would be too simple since there has nonetheless been some evolution of the human resource function. We are more concerned with the rate of its evolution. In conclusion, the author is considering the possible causes of this reality, and is looking for means to accelerate the evolutionary processes of this function.